Beyond Apple vs FBI: Implications for Singapore’s Smart Nation Project - Ang, Benjamin (2016)
The ongoing legal dispute between Apple Inc and the FBI, over accessing data on the iPhone of a deceased terror suspect, has been characterised as a conflict between security and privacy in the US. But it has also highlighted cybersecurity issues that have serious implications for Singapore’s Smart Nation initiative.